The correlation between alexithymia and communication skills among undergraduate pharmacy students - Amjad H. Bazzari; Firas H. Bazzari (Heliyon)
Awareness of self-emotions and the emotions of others is a key factor in ensuring that health professionals communicate effectively with patients. This is of great importance for pharmacists, who, as primary healthcare providers, depend daily on effective communication to ensure the best therapeutic outcomes. Here, we aimed to evaluate the level of alexithymia, its correlation with communication skills and associated demographics in a university sample of undergraduate pharmacy students. The study utilized a printed questionnaire consisting of three parts: demographics, the Perth Alexithymia Questionnaire (PAQ), and the Health Professionals Communication Skills Scale (HP-CSS). A total of 212 students participated with a mean age of 21.59 ± 3.38 years, including males (n = 88, 41.5 %) and females (n = 124, 58.5 %). The results revealed moderate alexithymia levels and relatively satisfactory communication skills among the participants. Males had higher alexithymia scores and lower communication skills compared to females. Self-reported GPA values negatively correlated with alexithymia level but not with communication skills. The level of alexithymia negatively correlated with total communication skills, irrespective of gender, and the four dimensions of communication. In conclusion, alexithymia is negatively correlated with communication skills among undergraduate pharmacy students, highlighting the necessity of emotional awareness in patient communication and care.